Learning playing - Silva, Luiz Antonio Pereira da (Journal of Physical Education (Maringá), 2008)
The author investigated the possibility of introducing dynamism to classroom. A proposal of teaching to read and write comprising the first and second grades of primary school was made. This enabled the teacher to know the children\’s development theories and adapted a work structure providing the children with motivation to leam and the teacher with knowledge to teach.